Model Pengembangan Local Culinary Tarvel Pattern di Desa Wisata Lerep - Setiawan Wibowo; Nur Farah Fajriaty Muchlis; Muhammad Yahya (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
This article aimed to findout a model for developing local culinary tourism patterns in the culinary tourism market segment and local food production in Lerep Village, Semarang Regency, especially Ungaran Barat sub-district using the Storynomics Tourism approach. The method used in this research was descriptive qualitative. The data had been taken from literatur study, observation and interviews with Lerep Village Government employees. It's finding showed thatthe development of culinary tourism activities in the Lerep Tourism Village use a model of developing local culinary tourism patterns based on local wisdom which is transformed into local menus created by the Lerep community. It was concluded that the modeling of local culinary travel patterns provides an insight for tourism actors and prospective tourists to determine travel activities, especially the local culinary world which has strong regional cultural characteristics. Keywords : Culinary, Local, Travel, Storynomic, Model